2015
DOI: 10.1111/apa.13180
|View full text |Cite
|
Sign up to set email alerts
|

Skin‐to‐skin contact reduces near‐infrared spectroscopy pain responses in premature infants during blood sampling

Abstract: This study showed that skin-to-skin contact between premature infants and their mothers during venepuncture had a pain-relieving effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1
15

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 24 publications
5
64
1
15
Order By: Relevance
“…If administration of vitamin K shot is a routine, this should occur soon after birth while the catecholamine levels are highest , preferably with the newborn infant skin‐to‐skin with the mother, as skin‐to‐skin contact has been shown to lower the baby's reaction to pain in the postpartum .…”
Section: The 9 Stages – a Breastfeeding Start Led By The Newborn Infantmentioning
confidence: 99%
“…If administration of vitamin K shot is a routine, this should occur soon after birth while the catecholamine levels are highest , preferably with the newborn infant skin‐to‐skin with the mother, as skin‐to‐skin contact has been shown to lower the baby's reaction to pain in the postpartum .…”
Section: The 9 Stages – a Breastfeeding Start Led By The Newborn Infantmentioning
confidence: 99%
“…Twenty‐five studies were included, and overall results indicated skin to skin care was an effective strategy that significantly minimised pain scores, behavioural changes and physiological responses during single painful procedures such as a heel lance in neonate infants (Johnston et al., ). Skin to skin contact between infants and their mothers has also been demonstrated to reduce near‐infrared spectroscopy pain responses in preterm infants during venipunctures (Olsson, Ahlsén, & Eriksson, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies show that skin‐to‐skin contact with their mothers reduces contralateral somatosensory activation during venipuncture in premature infants. This implies that skin‐to‐skin contact is an easy method by which parents can also get more involved in their infants’ care and pain management . Recent studies link aberrant emotional processing has been linked to developmental disorders with impairments in social interaction and communication such as autism spectrum disorder (ASD) .…”
Section: Overview Of Nirs Studies On Emotional Processing In Childrenmentioning
confidence: 99%
“…This implies that skin-to-skin contact is an easy method by which parents can also get more involved in their infants' care and pain management. 69 Recent studies link aberrant emotional processing has been linked to developmental disorders with impairments in social interaction and communication such as autism spectrum disorder (ASD). [70][71][72][73] Table 4 provides a detailed summary of the reviewed NIRS studies using the olfactory, tactile, and noxious stimuli for investigating emotional processing in children up to 2 years of age.…”
Section: Emotionally Relevant Olfactory Tactile and Noxious Stimulimentioning
confidence: 99%